IMPLEMENTASI PERATURAN PEMERINTAH NOMOR 53 TAHUN 2010 TENTANG PERATURAN DISIPLIN PEGAWAI NEGERI SIPIL DIKAITKAN DENGAN KEWENANGANPEMBINA APARATUR SIPIL NEGARA DI KOTA PEKANBARU - Okthafia Mawis; Mexsasai Indra; Evi Deliana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
Currently, the implementation of the work discipline as the initial capital in the smooth running of the tasks of civil servants, particularly Civil Servants, which is still minimal from what had been expected, the various forms of breach of discipline is still done employees. In the sense that Civil Servants are government employees who have met certain requirements, in the lift as employees Apparatus Civil State as fixed by the Trustees personnel officer to occupy the post of government as well as by applicable regulations. The applicable provision is exactly what is used as the legal basis for the Civil Servants itself. Making it as a form of discipline that must be complied with and run by Civil Servants. The discipline of Civil Servants is the ability of the employee to obey the obligations and avoids the prohibitions specified in laws and regulations and/or violated sentenced discipline.However, various attempts have been made for the enforcement of labor discipline, ranging from coaching to administration of sanctions for employees who committed the violation. In this case the writer wanted to know how the implementation of Government Regulation No. 53 Year 2010 Concerning Discipline of Civil Servants towards the authority of the Trustees of the Civil State Apparatus itself as well as how the efforts in overcoming the obstacles of the implementation of the punishment against the breach of discipline of Civil Servants.Keywords: Authority, Discipline, Law Enforcement